Legal aspect of fraud in yacht hull insurance – boats for sport and leisure - Damir Primorac (Zbornik Radova Pravnog Fakulteta u Splitu, 2015)
The authors analyze the application of the principle of good faith in performance of the yacht (boat for sport and leisure) hull insurance contract. In this work, the author indicate in which scope non-compliance with the above principles has effects on the performing of the principle of compensation as a fundamental principle of contractual relations maritime insurance, ie. the insurer's contractual obligation to pay compensation for damage to the insured. The subject of authors analysis in this paper refers to insurance and criminal lefal aspect of the legal consequences of committing insurance fraud in Croatian legislation with instructing and analysis of the relevant jurisprudence and comparative law specifics insurance solutions English legal doctrine and jurisprudence in particular in relation to the damage excluded from the insurance that arise as a result of wilful action by the insured („wilful misconduct“). The particularity of the application of foreign law and the interpretation of the relevant case law indicates to a problem of interpretation and understanding the purpose of standardizing legal solutions of different legal systems so authors point to the need of equalizing institute of the insured intention for assumption of insured event as excluded losses. With criminal legal analysis the specifics of Croation criminal legislation regarding the standardization of a separate criminal offence of fraud and insurance abuse authors evaluate positive solution provision art. 238 of the Criminal Code (came into force on January, 1 2013.), since in practice been previously created difficulties regarding the criminal offense qualification because the offender has exercised the same act of attempted fraud and completed criminal offense of insurance abuse.